Identifikasi Daging Ayam Kampung Segar Dengan Daging Ayam Kampung Basi Menggunakan Metode Learning Vector Quantization - Dennis Feliawan Aji (LPPM Universitas Mercu Buana Yogyakarta, 2020)
Kampong chicken meat is meat obtained from kampong chicken. kampong chicken meat is considered expensive because they take longer time to grow up, a lot of people cheat by selling stale kampong chicken meat. The characteristics used to identify the meat’s image are homogeneity, contrast, average and variants. The number of data used in this research consists of two classes, each class has 30 image data, the total data is 60 training data. Whereas for test data, each class used 20 test data with a total of 40 test data. During the training process using LVQ parameters, there were 2 best percentages of 90%, namely on alpha 0.001 with a dec alpha of 0.2 and alpha 0.01 with a dec alpha of 0.9. The identification performed using the final weight from alpha 0.01 and dec alpha 0.9 had an 90% accuracy level with 4 iterations. The best performance from 40 test data using this software was with alpha 0.01 and dec alpha 0.9, which reached 90%.